DAMPAK PANDEMI COVID-19 TERHADAP PERBEDAAN PERTUMBUHAN PRODUKSI INDUSTRI MIKRO DAN KECIL DI WILAYAH KORIDOR EKONOMI INDONESIA - Dunggio, Maryam; Lutfiati, Anis (Kinerja, 2022)
This study aims to prove the differences in the growth of Micro and Small Industry (IMK) production caused by the Covid-19 pandemic and differences in the Indonesian Economic Corridor (KEI) region. The study was conducted on IMK spread across 34 provinces in Indonesia based on data from BPS. The data analysis method used is comparative analysis using two way anova. The results of the study proved that: (1) there was a significant difference between the growth of IMK production before the pandemic and during the COVID-19 pandemic; (2) there is a significant difference between the growth of IMK production in each KEI; (3) interaksi KEI with the covid-19 pandemic has a significant impact on the difference in the growth of IMK production and (4) there is a difference in the average growth of IMK production in each KEI before the pandemic and during the covid-19 pandemic.